Contribution of retrotrapezoid/parafacial respiratory region to the expiratory-sympathetic coupling in response to peripheral chemoreflex in rats - Moraes, Davi José de Almeida; Dias, Mirela B.; Cavalcanti-Kwiatkoski, Roberta; Machado, Benedito Honório; Zoccal, Daniel Breseghello [UNESP] (American Physiological Society, 2012)
Central mechanisms of coupling between respiratory and sympathetic systems are essential for the entrainment between the enhanced respiratory drive and sympathoexcitation in response to hypoxia. However, the brainstem nuclei and neuronal network involved in these respiratory-sympathetic interactions remain unclear. Here, we evaluated whether the increase in expiratory activity and expiratory-modulated sympathoexcitation produced by the peripheral chemoreflex activation involves the retrotrapezoid nucleus/parafacial respiratory region (RTN/pFRG). Using decerebrated arterially perfused in situ rat preparations (60–80 g), we recorded the activities of thoracic sympathetic (tSN), phrenic (PN), and abdominal nerves (AbN) as well as the extracellular activity of RTN/pFRG expiratory neurons, and reflex responses to chemoreflex activation were evaluated before and after inactivation of the RTN/pFRG region with muscimol (1 mM). In the RTN/pFRG, we identified late-expiratory (late-E) neurons (n = 5) that were silent at resting but fired coincidently with the emergence of late-E bursts in AbN after peripheral chemoreceptor activation. Bilateral muscimol microinjections into the RTN/pFRG region (n = 6) significantly reduced basal PN frequency, mean AbN activity, and the amplitude of respiratory modulation of tSN (P < 0.05). With respect to peripheral chemoreflex responses, muscimol microinjections in the RTN/pFRG enhanced the PN inspiratory response, abolished the evoked late-E activity of AbN, but did not alter either the magnitude or pattern of the tSN reflex response. These findings indicate that the RTN/pFRG region is critically involved in the processing of the active expiratory response but not of the expiratory-modulated sympathetic response to peripheral chemoreflex activation of rat in situ preparations.